GAMBARAN PATOLOGI ANATOMI PADA BABI LANDRACE SUSPECT AFRICAN SWINE FEVER (ASF) DI KABUPATEN KUPANG - Simarmata, Yohanes T. R. M. R.; Tophianong, Tarsisius Considus; Amalo, Filphin Adolfin; Nitbani, Henny; Lenda, Victor (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2020)
African Swine Fever (ASF) is a viral disease that attacks pigs and to date has caused many pig deaths in Kupang Regency. ASF is caused by a double-stranded DNA virus from the Asfivirus genus and the Asfarviridae family. This research aims to determine the anatomical pathology of the swine landrace suspect ASF. Organ samples were collected from two male landrace pigs and two female landrace pigs, aged 7 months, from Oeltuah Village, Taebenu District and Tarus Village, Central Kupang District, Kupang Regency, NTT. Clinical examinations were carried out on sick animals that were found during the investigation, then necropsied on the dead animals were carried out and continued with anatomical pathology examinations at the Pathology Laboratory, Faculty of Veterinary Medicine, Nusa Cendana University. Anatomical pathology examinations are carried out by observing changes in the structure and appearance of the organs. The necropsy results showed sub-cutaneous ecchymosis hemorrhage in the abdomen, limbs and ears, gastric, intestinal and hepatic hemorrhage, hemorrhagic lymphadenitis in mesenteric lymph nodes, hyperemic splenomegaly, pteckie hemorrhage in the renal capsule,, multifocal hemorrhage in the renal medulla and pulmonary lobe. Based on the observation of clinical symptoms and changes in anatomical pathology, it can be concluded that the death of pigs was suspected to be caused by the suspect ASF.